PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL INTERAKTIF DENGAN METODE SILABA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK DISLEKSIA - -, Yeni Sulistyaningrum; Sujarwanto; Murtadlo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to develop interactive digital learning media based on the syllabic method to improve beginning reading skills among students with dyslexia. Initial observation at SDN Sogo 01, Balerejo, Madiun, revealed six students experiencing reading difficulties, such as confusing letters and struggling with syllable patterns (KV, KVK, VK, KKVK). Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research produced “BEM (Belajar Membaca/Learn to Read),” an application featuring seven syllable-based learning levels, word-level audio, automatic evaluation, and teacher–parent guidance tools. Validation results indicated that the media was highly valid, with expert scores of 97.89% (media) and 90.83% (content). Teacher assessments rated it highly practical, scoring 92.67%. Student responses reflected ease of navigation, dyslexia-friendly visuals, and enjoyable multisensory syllable-based learning. Effectiveness testing via the Wilcoxon signed-rank test yielded Z = -2.201 and a significance value of 0.028 (p < 0.05), indicating a significant improvement in students’ beginning reading ability after using the media. In conclusion, the developed interactive digital learning media based on the syllabic method is valid, practical, and effective for supporting beginning reading instruction for students with dyslexia in elementary schools.